MEANING-MAKING OF HEDGES IN THE GOSSIP COLUMN OF THE JAKARTA POST - Uswatun Hasanah; Ribut Wahyudi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
The present study investigates the use of hedges (vague language) as the meaning-making practice in the gossip column of the Jakarta Post. The daily newspaper is chosen due to pragmatic purposes, accessibility, and its national coverage. Adapting the framework of Lakoff (1973), Holmes (1990) and Hyland (1996a-b), this study focuses on the hedges’ functions and meanings in a gossip column (informal context), apart from an academic discourse (formal context) in which hedges are frequently discussed. This possibly leads to the diverse functions and meanings of the hedges’ occurrences within the discourse: through the employment of ‘epistemic modal’ (the expression of uncertainty) and ‘affective’ (the expression of solidarity) function. Further, the mostly-found hedges are the epistemic modal ‘about’ (five times) and the affective modal ‘think’ (four times) from six hedge categories. Eventually, it is also revealed that hedges used in the gossip column are to enhance the self-image and trend-setting identity of the celebrities, who indeed are involved in the discourse.